Research Progress on Prognostic Survival Assessment of Inflammatory Response Parameters in Ampullary Carcinoma - CHEN Ruiqiu; ZHANG Zhilei; JIA Yuming; PENG Li (Zhongliu Fangzhi Yanjiu, 2022)
Ampullary carcinoma is a rare malignant tumor of the digestive tract. Compared with other malignant tumors around the ampulla, its prognosis is significantly better, but the prognosis of some patients with ampulla cancer is unsatisfactory. Studies have confirmed that the systemic inflammatory response is closely related to the prognosis and efficacy of tumors, and the tumor microenvironment plays a vital role in tumor progression and prognosis. In recent years, inflammatory parameters and related prediction models have become a hot spot in predicting the prognosis and survival of ampullary cancer, and they have been confirmed to have certain predictive value. This article reviews the correlation between inflammatory parameters and prognosis of ampullary carcinoma and presents the possible progress for future research.